Information Technology in Special Library Environment - Sharma, Sumati (DESIDOC Journal of Library & Information Technology, 2003)
The paper outlines the features and impact of information technology (IT) on our society. Specifically it discusses in detail the role played by IT in special library environment. The changing IT environment and matching role of the reference librarian in 21 st century has been discussed.' As a case study it give: the complete spectrum of impact of IT on Defence Science Library (DSL), a specialised central library of DRDO functioning at DESIDOC. It discusses in detail the various library activities and services where DSL is making effective use of IT to provide better and enhanced services to its user. http://dx.doi.org/10.14429/dbit.19.6.3503